Sistem Pembelajaran Majelis Taklim Padhang Mbulan dalam Mewujudkan Learning Society - Moh. Syafi’il Anam (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2019)
There is a unique phenomenon in Jombang (Indonesia). The uniqueness of one of them is a society that is set in heterogeneous gathering of religious activities from night to early morning in the form of assembly Takim Maiyah Padang Mbulan. In this study, will be discussed about the learning system of the Assembly of Padhang Mbulan in realizing the Learning Society. This study used a qualitative approach with this type of case study research. The results showed that the Majelis Ilmi Maiyah Padhang Mbulan has its own learning system with its style, with the aim of deepening the tawheed and getting closer to Allah SWT. Learning methods in the form of interactive and communicative lectures with jokes or humor, deconstruction methods-reconstruction of values, questions and answers and discussion, free and open stage, analogy with the language of culture, demonstrations and methods The musical using the human media itself was assisted by other secondary media such as the utilization of various musical instruments both traditional and modern. The Learning society in the Assemblyman's assembly of Padhang Mbulan can be classified into three related phases i.e. input, process and output. Input in the form of public awareness (Jama'ah Maiyah) in learning and seeking knowledge. The process of entry intensity in attendance at the forum Maiyah. Output the form of works or programs produced Jama'ah Maiyah.